Compositional and Structural Difference of Fulvic Acid from Black Soil Applied with Different Organic Materials: Assessment After Three Years - Jian-ming LI; Jing-gui WU (Journal of Integrative Agriculture, 2013)
Knowledge of different effects of various organic materials on soil humic substance is important for both environmental safety and sustainable agriculture. A pot experiment was conducted at Jilin Agricultural University, Jilin Province in northeast China to discover the influence of herb residue, animal excrement, woody residue, animal remnant on fulvic acid (FA) composition and structure using differential thermal analysis-thermogravimetric (DTA-TG), fourier transform infrared spectroscopy (FTIR) and elemental analysis. DTA-TG showed the range of peak temperature in the first exothermic reaction increased following the trend: CK>herb residue>animal excrement>woody residue=animal remnant, and the most weight loss was observed in animal excrement. Moreover, the second exothermic reaction of CK- and animal excrement-FA was presented as double peaks, the order of weight loss in that area was animal remnant>CK>woody residue>animal excrement>herb residue. According to FTIR, herb residue displayed higher adsorption intensity at 2 950, 1 420, 1 240 and 1 030 cm−1, animal excrement was in reverse. At the same time, herb residue- and animal excrement-FA had an absorption peak at 1 720 cm−1, while other organic materials didn't have this peak. As elemental analysis showed, FA isolated from various treatments was significantly distinct. It was clearly shown from our results that FA composition and structure in amended soils may be affected in different ways and at various extents on dependence of the nature and origin of amendment.